EVALUASI PEMBELAJARAN DALAM PANDANGAN ISLAM DAN PSIKOLOGI - Haris Fakhriza; Muhammad Ramli (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
Learning evaluation is an important component in the education process. This study aims to integrate Islamic and psychological perspectives on learning evaluation. By analysing evaluation principles from both perspectives, this research proposes a holistic evaluation framework. Through file research method or library research with qualitative research type, the study comes from various literatures such as books, papers, articles or scientific journals, through searching through websites and internet sites. This research identifies similarities and differences between the two perspectives, and examines the implications of their practical application in the educational context. The results show that the integration of the two perspectives can result in a more comprehensive, relevant and meaningful evaluation for learners.